Impact of Assets and Sales on The Capital Development of Islamic Boarding School Cooperatives - Susilowati, Lantip; Febrianto, M. Nanang; Lestari, Lisa Yuni; Malik, Muhammad Khoirul (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2025)
This study examines the influence of assets and sales on the capital structure of the Husnul Khotimah Islamic boarding school cooperative using panel data from four business units between 2020 and 2023 (164 observations). Chow and Hausman tests confirm the Fixed Effect Model as the best specification. The findings show that assets of the HK Putra, HK Putri, and Economic Division units significantly affect capital, whereas the Pancalang unit’s assets do not. Regarding sales, only the HK Putra and Pancalang units exhibit significant effects on capital. Simultaneously, all independent variables significantly influence capital, supported by an Adjusted R² of 0,842, indicating that asset structure and sales performance are key determinants of capital strengthening in pesantren cooperatives. The study contributes to the global literature by offering empirical insights into how Islamic, community-based microeconomic institutions manage capital formation under limited external financing. This adds a new dimension to discussions on Islamic cooperative finance and the resilience of faith-based economic entities. Future research directions include: developing alternative Sharia-compliant capital models for pesantren cooperatives; conducting comparative studies with conventional cooperatives; incorporating profitability, efficiency, and risk-management variables; and examining the role of digital sales transformation in enhancing cooperative capital.